Brachial plexus paralysis in a patient with clavicular fracture, medico-legal implications - Fozzato, Stefania; Petrucci, Quirino Alessandro; Passeri, Alberto; Bianco Prevot, Luca; Accetta, Riccardo; Basile, Giuseppe (Acta Biomedica Atenei Parmensis, 2022)
Clavicular fractures make up 2.6-4% of all fractures in adults. The most frequent mechanism of injury is a fall with direct trauma to the shoulder during sports or road accidents. These fractures can have acute complications such as vascular lesions, nerve injuries, pneumothorax, and musculoskeletal injury. Primary brachial plexus injuries are rare events, both in the adult and paediatric population, have an incidence of less than 1% and are usually caused by direct compression of the fragments. We describe a case of midshaft clavicular fracture treated conservatively with a figure-eight bandage, associated with acute brachial plexus injury, and possible medico-legal repercussions thereof. It is important to recognize the progression of neurological deficits early on, in order for appropriate treatment to be undertaken promptly. Patients must be monitored and re-evaluated within few days after the injury to check the correct positioning of the brace, its degree of tolerability, and the possible onset of neurological deficits, because some clavicular fractures can be associated with compression of the brachial plexus.